Massively Parallel Sequencing Detected a Mutation in the MFN2 Gene Missed by Sanger Sequencing Due to a Primer Mismatch on an SNP Site - Neupauerová, Jana; Grečmalová, Dagmar; Seeman, Pavel; Laššuthová, Petra; Laššuthová, Petra (Annals of human genetics, 2016)
We describe a patient with early onset severe axonal Charcot-Marie-Tooth disease (CMT2) with dominant inheritance, in whom Sanger sequencing failed to detect a mutation in the mitofusin 2 (MFN2) gene because of a single nucleotide polymorphism (rs2236057) under the PCR primer sequence. The severe early onset phenotype and the family history with severely affected mother (died after delivery) was very suggestive of CMT2A and this suspicion was finally confirmed by a MFN2 mutation. The mutation p.His361Tyr was later detected in the patient by massively parallel sequencing with a gene panel for hereditary neuropathies. According to this information, new primers for amplification and sequencing were designed which bind away from the polymorphic sites of the patient's DNA. Sanger sequencing with these new primers then confirmed the heterozygous mutation in the MFN2 gene in this patient. This case report shows that massively parallel sequencing may in some rare cases be more sensitive than Sanger sequencing and highlights the importance of accurate primer design which requires special attention.
Keywords: mutace; GTP-fosfohydrolasy; Female; předškolní dítě; Pedigree; ženské pohlaví; mutační analýza DNA; jednonukleotidový polymorfismus; High-Throughput Nucleotide Sequencing; rodokmen; lidé; Polymorphism, Single Nucleotide; DNA Mutational Analysis; mitochondriální proteiny; DNA primery; Mutation; Charcotova-Marieova-Toothova nemoc; Male; Child, Preschool; vysoce účinné nukleotidové sekvenování; GTP Phosphohydrolases; DNA Primers; Charcot-Marie-Tooth Disease; mužské pohlaví; Mitochondrial Proteins; Humans